Eficácia da água eletrolisada acidificada na prevenção da ONMAB após exodontias: estudo experimental em ratos Wistars - Santos, Mhárllon Rutyna (2021)
Introduction: Bisphosphonate-related osteonecrosis of the jaws (BRONJ) is a complication associated with dental intervention and prolonged use of bisphosphonates (BF). Acidified Electrolyzed Water (AEA) is a substance that seems to improve tissue regeneration. Objective: to evaluate the effectiveness of (AEA) as an adjuvant in the treatment of BRONJ after lower molar extractions in Wistar rats. Material and methods: A split-mouth study was carried out in twelve Wistar rats (6 females and 6 males) received weekly intravenous injection of 0.3 mL of zoledronate (80 μg/kg in PBS) for 9 weeks and underwent tooth extraction. mandibular first and second molars in the eighth and ninth week, respectively. The Acidified Electrolyzed Water (AAG) group (right side of the mandible) was irrigated with AEA every three days while the control group (CG) (right side of the mandible) received no treatment after extractions. The animals were euthanized 6 weeks after the second extraction, the mandibles were dissected for clinical analysis with the data obtained submitted to statistical analysis with a significance level of 0.05. (Fischer's test). Results: Two males were lost during AEA therapy, leaving 10 animals, 6 females and 4 males. Inflammation was absent in all alveoli; bone sequestration was noted in all alveoli; suppuration was present in 3 sites of the GC group, epithelialization present in 5 GAEA alveoli and 2 GC. Comparison of bone exposure did not show statistically significant results. Conclusion: The results obtained were slightly favorable to the use of AEA, however, without statistical significance.